Pro-inflammatory miR-223 mediates the cross-talk between the IL23 pathway and the intestinal barrier in inflammatory bowel disease - Wang, Huiling; Chao, Kang; Ng, Siew Chien; Bai, Alfa Hc; Yu, Qiao; Yu, Jun; Li, Manying; Cui, Yi; Chen, Minhu; Hu, Ji-Fan; Zhang, Shenghong (Genome Biology, 2016)
The IL23/Th17 pathway is essential for the onset of inflammatory bowel disease (IBD), yet the specific mechanism by which this pathway initiates the disease remains unknown. In this study, we identify the mechanisms that mediate cross-talk between the IL23 pathway and the intestinal barrier in IBD. The downstream targets of the IL23 pathway were identified by RNA array profiling and confirmed by immunohistochemical staining. The role of miRNAs that interact with IL23 was explored in mice with TNBS-induced colitis. Claudin-8 (CLDN8), a multigene family protein that constitutes the backbone of tight junctions, was identified as a novel target of IL23 in IBD. CLDN8 was significantly downregulated in IBD patients with inflamed colonic mucosa, and in trinitrobenzene sulphonic acid (TNBS) induced colitis in mice. Therapeutic treatment of colitis in mice using an IL23 antibody restored CLDN8 abundance, in parallel with recovery from colitis. In addition, we identify miR-223 as a novel mediator of the crosstalk between the IL23 signal pathway and CLDN8 in the development of IBD. MiR-223 was upregulated in IBD, and its activity was regulated through the IL23 pathway. Antagomir inhibition of miR-223 reactivated CLDN8 and improved a number of signs associated with TNBS-induced colitis in mice. Our study characterizes a new mechanistic pathway in IBD, in which miR-223 interacts with the IL23 pathway by targeting CLDN8. Strategies designed to disrupt this interaction may provide novel therapeutic agents for the management of IBD.